Institutionalizing Performance in the Public Sector in LAC : The Case of Mexico - Manning, Nick; Arizti, Pedro; Senderowitsch, Roby (World Bank, Washington, DC, 2012)
Mexico, like other Economic Co-operation and Development (OECD) governments, is committed to improving the performance of the public sector. An important first step is to gather objective information that enables governments to measure progress towards achieving their policy and program goals. As well as potentially improving decision making by politicians and civil servants provided with higher quality information on the performance of departments/agencies and programs, this information can enhance transparency and accountability to the public and the legislature. The Government of Mexico (GoM)'s new results-based budgeting initiative is anchored in a new legal framework, establishing the Performance Evaluation System or Sistema de Evaluacion del Desempeno (SED) that will provide data on the performance of publicly-financed programs and organizations as inputs to the budget cycle. These performance data include consolidated data from program evaluations or other sources on the outputs and impact/effectiveness of public expenditures; and data on the quality of public management, which is the focus of a new Management Improvement Program.